Transcriptional profiling of articular cartilage in a porcine model of early post‐traumatic osteoarthritis. Issue 1 (3rd August 2017) - Sieker, Jakob T.; Proffen, Benedikt L.; Waller, Kimberly A.; Chin, Kaitlyn E.; Karamchedu, Naga Padmini; Akelman, Matthew R.; Perrone, Gabriel S.; Kiapour, Ata M.; Konrad, Johannes; Murray, Martha M.; Fleming, Braden C.
ABSTRACT: To identify the molecular pathophysiology present in early post‐traumatic osteoarthritis (PTOA), the transcriptional profile of articular cartilage and its response to surgical PTOA induction were determined. Thirty six Yucatan minipigs underwent anterior cruciate ligament (ACL) transection and were randomly assigned in equal numbers to no further treatment, reconstruction or ligament repair. Cartilage was harvested at 1 and 4 weeks post‐operatively and histology and RNA‐sequencing were performed and compared to controls. Microscopic cartilage scores significantly worsened at 1 ( p = 0.028) and 4 weeks ( p = 0.001) post‐surgery relative to controls, but did not differ between untreated, reconstruction or repair groups. Gene expression after ACL reconstruction and ACL transection were similar, with only 0.03% (including SERPINB7 and CR2 ) and 0.2% of transcripts (including INHBA ) differentially expressed at 1 and 4 weeks respectively. COL2A1, COMP, SPARC, CHAD, and EF1ALPHA were the most highly expressed non ribosomal, non mitochondrial genes in the controls and remained abundant after surgery. A total of 1, 275 genes were differentially expressed between 1 and 4 weeks post‐surgery. With the treatment groups pooled, 682 genes were differentially expressed at both time‐points, with the most significant changes observed in MMP1, COCH, POSTN, CYTL1, and PTGFR . This study confirmed the development of a microscopic PTOA stage after ACL surgery in the porcine model. Upregulation of multiple proteases (including MMP1 and ADAMTS4 ) were found; however, the level of expression remained orders of magnitude below that of extracellular matrix protein‐coding genes (including COL2A1 and ACAN ). In summary, genes with established roles in PTOA as well as novel targets for specific intervention were identified. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:318–329, 2018.